UMPSA welcomes PERHEBAT Empowerment Agenda for TVET Ecosystem - Nur Hartini, Mohd Hatta (UMPSA, 2025)
KUALA LUMPUR, 15 October 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), as a strategic partner of the Armed Forces Ex-Servicemen Affairs Corporation (PERHEBAT), welcomes the announcement of the PERHEBAT Transformation Plan 2026–2035 launched by the Minister of Defence, Yang Berhormat Dato’ Seri Mohamed Khaled Nordin, to strengthen its role as the Driver of National Heroes’ Economic Sustainability, in line with its responsibility to ensure the continuous well-being of future retirees and military veterans.